The state of the left ventricular-arterial coupling depending on the left ventricular ejection fraction in patients with acute myocardial infarction. (14th October 2021) - Salyamova, L; Khromova, A; Kvasova, O; Burko, N; Makarova, K
Abstract: Objective: To conduct a comparative analysis of the indicators of left ventricular-arterial coupling (LVAC) in patients with primary acute myocardial infarction with ST segment elevation (STEMI), depending on the initial level of the left ventricular ejection fraction (EF). Methods: The study included 148 patients with STEMI (mean age 51.5 [CI% 50.1; 52.9] years) in the first 24–96 hours from the disease onset. An inclusion criterion was the presence of hemodynamically significant stenosis of only one coronary artery according to the coronary angiography results. On days 7–9th from the disease onset, the patients underwent standard echocardiography on the MyLab device (Esaote, Italy) with the determination of the end diastolic volume (EDV), end systolic volume (ESV), EF and the subsequent calculation of LVAC: arterial elastance (Ea), left ventricular elastance (Ees), including those reduced to body surface area (Ea/BSA and Ees/BSA), LVAC index (Ea/ Ees). In accordance with the LVEF values, the patients were divided into 3 groups. The 1st group included 79 people with preserved EF (≥50%), the 2nd group – 53 patients with mid-range EF (40–49%); Group 3 consisted of 16 patients with reduced EF (<40%). The compared groups were matched by age, sex, anthropometric data, and treatment. Results: In the 1st group, the Ea indicator was 1.8 [CI% 1.7; 1.9], in group 2 – 2.0 [CI% 1.8; 2.1], in the third group – 2.2 [CI% 1.9; 2.5] mm Hg/ml (p1-3 = 0.01). The Ees indicator in the comparison groups was 2.2 [CI% 2.1; 2.4], 1.7 [CI% 1.5; 1.9] and 1.2 [CI% 0.9; 1.5] mm Hg/ml, respectively (p1-2-3 <0.01). The Ea/BSA index in the 1st group was 0.92 [CI% 0.85; 1.0], in the 2nd group – 1.0 [CI% 0.94; 1.13], in the third group – 1.16 [CI% 0.99; 1.33] mm Hg/ml/m 2 (p1–3 = 0.01). The Ees/BSA indicator in the comparison groups was 1.16 [CI% 1.08; 1.24], 0.88 [CI% 0.79; 0.98] and 0.64 [CI% 0.46; 0.82] mm Hg/ml/m 2, respectively (p1-2-3 <0.01). The Ea/Ees index was the smallest in the 1st group – 0.8 [CI% 0.8; 0.9]; higher in the 2nd group – 1.2 [CI% 1.1; 1.3]; the maximum values were registered in the 3rd group – 1.9 [CI% 1.7; 2.0] (p1-2-3 <0.0001). Conclusions: In STEMI patients with mid-range and reduced EF, high values of the LVAC index were revealed, which is due to a decrease in left ventricular elastance due to impaired LV contractility. Funding Acknowledgement: Type of funding sources: None.